FAKTOR-FAKTOR YANG MEMENGARUHI KECEMASAN IBU PRE OPERASI SECTIO CAESAREA (SC) DI RUMAH SAKIT UMUM DAERAH SIDIKALANG KABUPATEN DAIRI - Risdiana Melinda Naibaho (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Sectio caesarea is needed as an effort to deliver to save the mother and the fetus, althought at this time the trend of childbirth with sectio caesarea is increasing from year to year, however, every mother who is going to undergo labor with surgery always feels anxiety when facing sectio caesarea surgery.This type of research is a descriptive survey to describe the factor,s that influence the anxiety of pre caesarean section mothers.The population is pregnant women who will give birth by sectio caesarean surgery at the Hospital General Sidikalang Dairi Regency. Sampling with accidental sampling tehnique with a total sample of 55 preoperative caesarean section patiens was based on certain considerations made by the reseachers themselves, based on the average number of caesarean sectins in one year, as many as 1572 people, so that the average monthly number is 131 peple. The data collection tehnique was done through interviews using a questinnaire. The data obtained were analyzed by univariate, bivarriate with chi square p-value 95% ( ? = 0,05).The results of this study indicate that age (p-value = 0,003), education (p-value = 0,000),parity (p-value = 0,002),support (p-value = 0,000),trauma (p-value = 0,003),knowledge (p-value = 0,000),affect anxiety pre operative mother for section caesarea.Sugegestins for families to be given information about the secti caesarean action to be able to provide tigter support to increase confidence in preoperative mothers to increase maternal knowledge, to health workers, to be able to provide information and support to preoperative mothers to make mothers feel comfortable